Congenital sideroblastic anaemia in two girls. Issue 6 (June 1991) - Dolan, G; Reid, M M
Abstract : Transfusion dependent congenital sideroblastic anaemia occurred in infancy in two unrelated girls. One girl developed early organ failure which was not prevented by standard chelation treatment. The combination of modest iron burden and putative intrinsic mitochondrial dysfunction could have accounted for the clinical picture. The other girl remained well, receiving regular transfusion and standard chelation treatment. She had normal liver function and no other evidence of organ damage. The syndrome is unlikely to be due to extreme lyonisation in carriers of the usual X-linked condition. The contrasting clinical patterns seen in these two patients suggest that transfusion dependent congenital sideroblastic anaemia may comprise a heterogeneous group of disorders. It is suggested that such children be carefully monitored for evidence of increasing iron overload so that organ damage can be prevented.